MENINGKATKAN PRESTASI BELAJAR SISWA SEKOLAH DASAR MELALUI PENGGUNAAN MEDIA AUDIO VISUAL - Aurelius Fredimento; Richardus Muga; Gregorius Sebo Bito (Prima Magistra: Jurnal Ilmiah Kependidikan, 2024)
One of the problems experienced by Catholic Religious Education (PAK) teachers at SDI Pelibaler is the unsatisfactory learning achievement of students.   Overcoming these problems, audio-visual media is offered as an alternative learning media which, if managed properly in the learning process, will have a significant effect on improving the learning achievement of Class V SDI Pelibaler students. The research subjects in this study were fifth grade students of SDI Pelibaler, totaling 13 students. The data in this study were obtained from the observation of students' activities and the final test instrument of each cycle. This research data was analyzed descriptively qualitative. The results showed that the application of audio-visual media can improve students' learning achievement. In the pre-cycle, students who completed their learning reached 46.15% while those who did not complete 53.84%. In cycle 1, students who were complete were 84.61% and those who were not complete were 15.39%. In cycle 2, students who were complete reached 100%. Based on the results of this study, it can be concluded that the use of audio-visual media can improve the learning achievement of Grade V students of SDI Pelibaler, Doren District, Sikka Regency.